Medical Informatics in Morocco - Bouhaddou, O.; Bennani Othmani, M.; Diouny, S. (Yearbook of Medical Informatics, 2013)
Objectives: Informatics is an essential tool for helping to transform healthcare from a paper-based to a digital sector. This article explores the state-of-the-art of health informatics in Morocco. Specifically, it aims to give a general overview of the Moroccan healthcare system, the challenges it is facing, and the efforts undertaken by the informatics community and Moroccan government in terms of education, research and practice to reform the country's health sector.Methods: Through the experience of establishing Medical Informatics as a medical specialty in 2008, creating a Moroccan Medical Informatics Association in 2010 and holding a first national congress took place in April 2012, the authors present their assessment of some important priorities for health informatics in Morocco.Results: These Moroccan initiatives are facilitating collaboration in education, research, and implementation of clinical information systems. In particular, the stakeholders have recognized the need for a national coordinator office and the development of a national framework for standards and interoperability.Conclusion: For developing countries like Morocco, new health IT approaches like mobile health and trans-media health advertising could help optimize scarce resources, improve access to rural areas and focus on the most prevalent health problems, optimizing health care access, quality, and cost for Morocco population.
Keywords: Medical informatics; Morocco; mobile health; developing countries